KASUS PERLINDUNGAN HAK PENDIDIKAN ANAK DALAM TINJAUAN HUKUM ISLAM DAN HAM - Supriyadi Supriyadi (JIE (Journal of Islamic Education), 2018)
Human rights are a reflection of carrying out Islamic law in order to realize the nature of universal human benefit. Islam considers that human rights are in accordance with sharia principles, namely protecting one's right to life. This is a strong basis for the study of Islamic law in contributing to the development of human rights principles in society. Studying Islamic law in Indonesia in a multidisciplinary perspective of interesting Islamic sciences to follow, so that the legal paradigm especially in Islamic teachings is not only normative-theological, but integrated with many scientific fields both in the sciences and the humanities. Contemporary global issues require observers and Islamic law reviewers to seriously review Islamic law in depth, one of the issues that is currently interesting and has become a topic of discussion among many is the issue of the protection of human rights. This paper will conduct a multidisciplinary theoretical study of Islamic sciences about how Islamic law concepts in protecting human rights. Departing from this, a comparative study between legislation and texts (verses) both in the al-Qur’an and the al-hadith, the comparative-critical analysis method makes it easier for the author to find substance in terms of answering the problem statement in this paper.